The Role of Laboratory Parameters in Assessment of Disease Severity and Outcome in COVID-19 patients – A Retrospective Study in a Tertiary Care Centre in Southern India - B, Rajeshwari; Shanmugam, Salapathi; Mathan, Anila; R, Dhananjayan; B, Isabella Princess; K, Selvan; Ghosh, Mitra (Annals of Pathology and Laboratory Medicine, 2021)
Background: Corona Virus Disease 2019 (COVID19) is a global pandemic, the outbreak of which started in China in December 2019. Apart from the clinical symptoms and pulmonary computed tomography (CT) findings, several laboratory biomarkers also play an important role in management of these patients so that immediate attention can be given to those with severe disease and critical illness. In this study we tried to find the association of various laboratory biomarkers in COVID-19 patients, analyzed around the time of admission, with the severity of the disease and outcome. Methods: In this study 1048 COVID19 positive cases admitted in our hospital during the study period from April 2020 to October 2020 were included. The cases were clinically assessed based on the severity of the disease at the time of presentation and during the course in hospital and categorized into 3 categories as Mild, Moderate and Severe according to our hospital protocol for management of COVID 19 patients. The clinical and laboratory data were retrieved from electronic medical records. The levels of various laboratory parameters at/around the time of admission were compared with clinical categories, severity and outcome of the disease. Result: We found a statistically significant association of severity and outcome of COVID-19 with various laboratory parameters. There were significantly higher levels of D-dimer, LDH, CK, CRP, Sr Ferritin, cTnI, NT pro BNP, PCT, IL-6 and lower ALC in non survivors compared to survivors and in severe disease compared to mild disease with a p value of <0.05. Conclusion: In this study we propose that along with the initial clinical assessment, age and concurrent co-morbidities of COVID-19 patients which determine the need for their admission to ICUs, the initial assessment of several laboratory parameters is helpful in triaging the patients who need intensive care so that proper allocation of resources can be done.